Next-Generation Sequencing as First-Line Diagnostic Test in Patients With Disorders of Sex Development? - Rey, Rodolfo Alberto (2022)
Disorders of sex development (DSD) are a group of highly heterogeneous disorders presenting mainly at birth or at pubertal age, characterized by discordance between chromosomal, gonadal, and/or genital sex. Newborns usually present with ambiguous genitalia while adolescents present with atypical or downright absent pubertal development (1)...